We Are Aztlan! : Chicanx Histories in the Northern Borderlands - García, Jerry, 1963- (Book collections on Project MUSE., 2017)
"Mexican Americans/Chicana/os/Chicanx form a majority of the overall Latino population in the United States. In this collection, established and emerging Chicanx researchers diverge from the discipline's traditional Southwest focus to offer academic and non-academic perspectives specifically on the Pacific Northwest and the Midwest. Their multidisciplinary papers address colonialism, gender, history, immigration, labor, literature, sociology, education, and religion, setting El Movimiento (the Chicanx movement) and the Chicanx experience beyond customary scholarship and illuminating how Chicanxs have challenged racialization, marginalization, and isolation in the northern borderlands."--Provided by publisher.